Analysis of a segmented locking ring for shell-bottom connection in pressure vessels. (2018) - Strozzi, A.; Bertocchi, E.; Mantovani, S.
Abstract: A simplified mechanical analysis is carried out for a specific closure system of a pressure vessel, consisting of a segmented locking ring, partially inserted into an annular slot; the ring portion protruding from the slot supports the vessel bottom; sealing is achieved by placing a copper gasket between the ring and the bottom. An approximate contact reaction is assumed, that is formed by a distributed constant linear force and by concentrated forces at the extremities of the ring-slot contact. Analytical expressions of the ring internal forces are provided. A numerical example is presented.